Geological and geochemical constraints on the genesis of the Xiqianluzi Pb–Zn polymetallic deposit in Beishan, Gansu Province, NW China. Issue 9 (29th May 2022) - Yang, Yongchun; Liu, Jiajun; Carranza, Emmanuel John M.; Ding, Shuhong; Fan, Xinxiang; Wang, Genhou; Zhang, Litao; Yao, Shuangfu; Zhao, Jichang; Li, Shengdong; Da, Rui; Yang, Zhenxi; et al.
Abstract : The Xiqianluzi Pb–Zn polymetallic deposit is located in the southeast of the southern Beishan belt, whereas the ore‐forming metal sources are still unclear. Its Pb–Zn ore bodies mainly occur in the Changcheng system Qianluzigou Group metamorphic clastic rocks, showing zonation of Cu–Zn–Pb metals from deep to surface. The ore structures are mainly banded, massive and veined, which have the characteristics of syngenetic sedimentation. Au mineralization in silty slate is obviously controlled by WNW–ESE‐trending faults, and occurs as veined or lenticular type. The Pb, Zn, Cu, and Au are mainly enriched in quartz or siliceous veins. The biotite granodiorites are enriched in Si, Na, Rb, Ba and K, with A/CNK values less than 1.1, and depleted in Nb, P, Ti. They belong to calc‐alkalic series and weak peraluminous I‐type granite, formed in a post‐collision extensional environment and characterized by crust–mantle mixed source. The sulphide minerals in the Pb–Zn ores have δ 34 S values in the range of 17.7‰–21.0‰ with average of 19.2‰, reflecting seawater sulphate origin of sulphur. The sulphur of Pb–Zn ores was likely transformed from S 6+ to S 2− by thermochemical sulphate reduction. The Pb isotopic compositions of sulphide minerals in the Pb–Zn ores have 206 Pb/ 204 Pb ratios of 16.837–17.001, 207 Pb/ 204 Pb ratios of 15.437–15.557, and 208 Pb/ 204 Pb ratios of 36.377–36.889. In contrast, sulphide minerals in Au ores have δ 34 S values (5.4‰–7.6‰, with average of 6.5‰) lower than those of sulphide minerals in the Pb–Zn ores. The δ 34 S values of sulphide minerals in the Au ores are consistent with those of sulphide minerals in the Late Permian–Middle Triassic magmatic hydrothermal gold deposits in the southern Beishan belt, which imply a magmatic source for sulphur. Sulphide minerals in the Au ores have higher lead isotopic ratios, including 206 Pb/ 204 Pb of 18.249–18.325, 207 Pb/ 204 Pb of 15.583–15.598, and 208 Pb/ 204 Pb of 38.023–38.366, compared to those in the Pb–Zn ores. Geological and isotopic features indicate that the Xiqianluzi Pb–Zn polymetallic deposit comprises two mineralization types; namely, its Pb–Zn ores can be considered as Mesoproterozoic sedimentary exhalative type, while its Au ores are magmatic origin. These show that Au mineralization was closely related to the magmatic hydrothermal activities, and thus Au ores can be classified as Late Permian–Early Triassic magmatic hydrothermal Au mineralization. Abstract : Xiqianluzi Pb–Zn polymetallic deposit underwent two types of mineralization, first the Mesoproterozoic sedimentary exhalative Pb–Zn mineralization and second the Late Permian–Early Triassic magmatic hydrothermal Au mineralization.